A hybrid spiral-bobbin eddy current testing probe for detection of crack of arbitrary orientation in steam generator tubes. Issue 3 (4th May 2022) - Zhao, Yingsong; Wang, Meng; Han, Jie; Deng, Jie; Zhu, Yulong; Cai, Wenlu; Chen, Hong-En; Chen, Hui; Chen, Zhenmao
ABSTRACT: This paper presents a new hybrid spiral-bobbin probe (S-bobbin probe) of transmitting-receiving (TR) mode for efficient eddy current testing (ECT) of steam generator tubes in nuclear power plants. The new probe of novel configuration can solve the major drawback of the conventional bobbin type ECT probe, i.e., insensitive to circumferential cracks. The excitation coil of the new probe consists of 2 coil segments of spiral geometry and 2 coil segments of half circle geometry which are sequentially connected to form a full coil loop. To acquire defect signal of low lift-off noise, the TR probe mode is adopted and the shape of the pick-up coil is selected the same as that of the excitation coil. As the S-bobbin probe can induce eddy currents in two different directions, it can detect cracks in SG tubes of arbitrary orientations. In order to demonstrate the validity and efficiency of the new S-bobbin probe, simulations and experiments were carried out with a prototype S-bobbin probe and tube specimens with circumferential or axial artificial cracks. The simulation and experimental results agree well, and both of them reveal that a crack in any direction can be properly detected and evaluated by using the new probe.